2014
DOI: 10.3762/bjnano.5.15
|View full text |Cite
|
Sign up to set email alerts
|

Change of the work function of platinum electrodes induced by halide adsorption

Abstract: SummaryThe properties of a halogen-covered platinum(111) surface have been studied by using density functional theory (DFT), because halides are often present at electrochemical electrode/electrolyte interfaces. We focused in particular on the halogen-induced work function change as a function of the coverage of fluorine, chlorine, bromine and iodine. For electronegative adsorbates, an adsorption-induced increase of the work function is usually expected, yet we find a decrease of the work function for Cl, Br a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 40 publications
8
131
0
2
Order By: Relevance
“…This unusual behavior can be explained as Roman et al [52] suggested, large atoms such as iodine leads to a considerable buildup of charge in the adsorbates-surface bonding regions, and an accompanying electron depletion region far from the surface which creates a net dipole on the adsorbates that in turn promotes a decrease in the work function. The adsorption of chlorine, bromine on Al 2 Au (110) surface increases the work function at low coverages.…”
Section: Work Function Shiftmentioning
confidence: 89%
See 4 more Smart Citations
“…This unusual behavior can be explained as Roman et al [52] suggested, large atoms such as iodine leads to a considerable buildup of charge in the adsorbates-surface bonding regions, and an accompanying electron depletion region far from the surface which creates a net dipole on the adsorbates that in turn promotes a decrease in the work function. The adsorption of chlorine, bromine on Al 2 Au (110) surface increases the work function at low coverages.…”
Section: Work Function Shiftmentioning
confidence: 89%
“…However, as mentioned previously, adsorbates induced surface relaxation of the substrate can also results in a little bit of work function change. The different signs for dipole moment changes and the corresponding work function changes are difficult to interpret with the directly proportional relationship proposed by Roman et al [52] To better illustrate this, we further notice that there is a small intercept in the fitted line. If the calculated dipole moment changes are also very small, this small intercept may cause non-correspondence sign of the work function changes and dipole moment changes.…”
Section: Work Function Shiftmentioning
confidence: 94%
See 3 more Smart Citations